Interpretasi Frasa Harmful Contamination Dalam Pasal 7(1) Moon Agreement 1979 Sebagai Upaya Pencegahan Kontaminasi Bulan (RechtJiva, 2025)
This research is motivated by the absence of an explicit definition of the phrase "harmful contamination" in Article 7(1) of the 1979 Moon Agreement, which results in weak regulatory provisions regarding the prevention of harmful contamination of the lunar environment and other celestial bodies in the solar system. The urgency of this research lies in the lack of a clear definition, which leads to ambiguous interpretations and opens up space for varying understandings of the term. This study aims to analyze and interpret the meaning of harmful contamination within the framework of space law and to assess the extent to which current lunar exploration activities align with that interpretation. To address these issues, this research adopts a normative juridical method with a statutory and conceptual approach. The findings indicate that existing legal instruments do not provide an explicit definition of harmful contamination, thereby creating a normative gap in the environmental protection of celestial bodies. Accordingly, this study proposes a more comprehensive interpretation, namely: “biological or non-biological contamination resulting from the introduction of unwanted foreign materials into the lunar environment and other celestial bodies in the solar system due to human activities, which potentially disrupt the environmental balance of the Moon, either directly or indirectly.” Based on this interpretation, it is found that current lunar exploration practices are not yet fully aligned with the ideal understanding of harmful contamination.